L’Union Européenne et la Crise Gréco-Turque d’Imia - Catsiapis, Jean (Études helléniques / Hellenic Studies, 1996)
During the night of January 30, 1996, Greece and Turkey were on the verge of war for Imia (Kardak for Turks), an uninhabited Aegean islet located between the Turkish city of Bodrum and the Greek island of Kalymnos. Both countries claimed sovereignty on Imia. Thanks to the American intervention, an armed conflict between two NATO members was avoided. Oddly enough, the EU, in which Greece enjoys full membership and Turkey seeks the same status, remained a passive observer of the events on Imia. The various EU institutions waited for the outcome of the crisis before taking a position on this Greek-Turkish dispute.